Peningkatan Teori Akuntansi Syariah Di Indonesia - Hardini Ariningrum; Fatriola Yoda Sutrahti (STAI Al-Mas'udiyah, 2022)
Along with the development of Islamic banks in Indonesia, the Muslim community implements Islamic sharia in socio-economic life, more and more Islamic business institutions carry out their operational and business activities based on sharia principles. Transaction recording and financial reporting applied to Islamic business institutions which later developed into sharia accounting. The development of accounting as a branch of social science has experienced a very basic and meaningful shift in values, especially regarding the underlying theoretical framework that is guided by changes that occur in people's lives. Another philosophy of accounting is accounting follows the business. In this context, the development of accounting is a response and evaluation of business developments. The purpose of this study is to examine the development of Islamic accounting theory that already exists in Indonesia. The method used in this research is ex post facto analysis through urf as the main basis. This study finds that the ideal Islamic accounting theory consists of rules covering aspects of aqidah, amaliah law, and morals. The implication is that Islamic financial statements must have a number of material and non-material properties. Thus, sharia accounting theory is used to maintain Allah's sharia, both conceptually and practically.